Reduced-Size Crossed-Dipole Antenna - Kedze, Kam Eucharist; Wang, Heesu; Kim, Youngwook; Park, Ikmo (2019 International Symposium on Antennas and Propagation, ISAP 2019 - Proceedings, 2019)
This paper proposes a reduced-size crossed-dipole antenna that comprises two printed crossed-dipole arms, a ground plane, and a pair of vacant quarter printed rings to generate circularly polarized (CP) radiation. The reduced-size crossed dipole is similar to the conventional crossed dipole but differs in that half of the crossed dipole is rotated 90 degrees. By rotating half of the crossed dipole, the area covered by the conventional crossed dipole is reduced by half, resulting in a compact, small-size antenna that generates CP radiation with a performance nearly identical to that of conventional crossed dipoles in terms of axial ratio (AR) bandwidth and radiation patterns. This performance is discussed and confirmed computationally. The reduced-size crossed-dipole antenna with overall dimensions of 33 mm × 54.6 mm × 29 mm (0.269λo × 0.446λo×0.2368λo at 2.45 GHz) has a |S11| < -10 dB bandwidth of 2.2-2.86 GHz (26.08%), a 3-dB AR bandwidth of 2.3-2.6 GHz (12.21%), a broadside gain of 7.85-7.98 dBic, and a radiation efficiency of > 90%.
Keywords: Antenna miniaturization; broadband; Circularly polarized; Crossed dipoles; Crossed-dipole antenna; Ground planes; Radiation efficiency; Reduced size; antenna miniaturization; broadband; circular polarization; crossed dipole